Anti‐disialosyl‐immunoglobulin M chronic autoimmune neuropathies: a nationwide multicenter retrospective study. (29th August 2022) - Peillet, Claire; Adams, David; Attarian, Shahram; Bouhour, Françoise; Cauquil, Cécile; Cassereau, Julien; Chanson, Jean‐Baptiste; Cintas, Pascal; Creange, Alain; Delmont, Emilien; Fargeot, Guillaume; Genestet, Steeve; et al.
Abstract: Background and purpose: In this retrospective study involving 14 university hospitals from France and Switzerland, the aim was to define the clinicopathological features of chronic neuropathies with anti‐disialosyl ganglioside immunoglobulin M (IgM) antibodies (CNDA). Results: Fifty‐five patients with a polyneuropathy evolving for more than 2 months and with at least one anti‐disialosyl ganglioside IgM antibody, that is, anti‐GD1b, ‐GT1b, ‐GQ1b, ‐GT1a, ‐GD2 and ‐GD3, were identified. Seventy‐eight percent of patients were male, mean age at disease onset was 55 years (30–76) and disease onset was progressive (82%) or acute (18%). Patients presented with limb sensory symptoms (94% of cases), sensory ataxia (85%), oculomotor weakness (36%), limb motor symptoms (31%) and bulbar muscle weakness (18%). Sixty‐five percent of patients had a demyelinating polyradiculoneuropathy electrodiagnostic profile and 24% a sensory neuronopathy profile. Anti‐GD1b antibodies were found in 78% of cases, whilst other anti‐disialosyl antibodies were each observed in less than 51% of patients. Other features included nerve biopsy demyelination (100% of cases), increased cerebrospinal fluid protein content (75%), IgM paraprotein (50%) and malignant hemopathy (8%). Eighty‐six percent of CNDA patients were intravenous immunoglobulins‐responsive, and rituximab was successfully used as second‐line treatment in 50% of cases. Fifteen percent of patients had mild symptoms and were not treated. CNDA course was progressive (55%) or relapsing (45%), and 93% of patients still walked after a mean disease duration of 11 years. Conclusion: Chronic neuropathies with anti‐disialosyl ganglioside IgM antibodies have a recognizable phenotype, are mostly intravenous immunoglobulins‐responsive and present with a good outcome in a majority of cases.